Programação de caminhões de múltiplos tipos no transporte de derivados de petróleo para a construção de rodovias - Costa Filho, José Luciano Lopes da (2014)
The truck scheduling problem is an important topic in the companies’ fleet management. Many companies face difficulties to manage their vehicles due to several variables inherent to the management process, such as the optimal fleet size, multiple types of trucks available, trucks capacity, the technical information from the client’s construction site and trips scheduling. In terms of the transportation of oil products, there are many operational characteristics that make the truck scheduling difficult. Despite the extensive literature about vehicle scheduling, truck scheduling for this type of transport is limited. The purpose of this research study was to develop an Integer Programming model to optimize the multi-type truck scheduling for the transportation of oil products for road construction sites. Data from a real company were gathered. A model that aimed to minimize the truck fleet available was developed. The method used has minimized the available fleet in the period under review. The development of key performance indicators allows to evaluate the quality of the solutions created.